2020
DOI: 10.1007/s10763-020-10061-1
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Coordination of Dialogic and Authoritative Discourses Promoting Specific Goals in Socioscientific Issue-Based Teaching

Abstract: The integration of socioscientific issues (SSI) into science teaching requires that teachers manage classroom discussions in which various perspectives are considered and students' contributions are recognized. The present study aimed to provide knowledge of how classroom discussions on SSI can be structured and implemented to pursue specific teaching purposes. In this study, two secondary science teachers' employment of communicative approaches during four discussions on SSI was analysed. In the studied conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this regard, the integration of socio-scientific issues-based tasks in the classroom is suitable, because it allows students to work in an interdisciplinary manner and stimulates critical thinking (Karpudewan & Roth, 2018;Wan & Bi, 2019;Wang et al, 2017). Such discussions about socio-scientific issues should include interrelations between politics, economics, and environment at different levels and be critical as well as complex in order to enhance the reconstruction of their conceptions (Bossér & Lindahl, 2020;Chu & Treagust, 2014;Sormunen, Juuti, & Lavonen, 2019;Wan & Bi, 2019;Wang et al, 2018). In our study, we observed that students believed in controlling the world population to remain within the planetary boundaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the integration of socio-scientific issues-based tasks in the classroom is suitable, because it allows students to work in an interdisciplinary manner and stimulates critical thinking (Karpudewan & Roth, 2018;Wan & Bi, 2019;Wang et al, 2017). Such discussions about socio-scientific issues should include interrelations between politics, economics, and environment at different levels and be critical as well as complex in order to enhance the reconstruction of their conceptions (Bossér & Lindahl, 2020;Chu & Treagust, 2014;Sormunen, Juuti, & Lavonen, 2019;Wan & Bi, 2019;Wang et al, 2018). In our study, we observed that students believed in controlling the world population to remain within the planetary boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…The creative problem solving (CPS) method (Huang et al, 2019) is suitable for this purpose as it develops solutions of the complex real-world problem not starting from the problem, but backwards from the ideal situation to the problem. Also, teaching approaches, which involve active student participation in topic-related problem-solving processes and give them the freedom to critically reflect on different perspectives, allow students to better understand complex environmental topics (Bossér & Lindahl, 2020;Huang et al, 2019;Karpudewan & Roth, 2018;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interaction and discourse are key factors that have a significant impact on the teaching and learning of science. Bosser and Lindahl (2021) indicates that a teacher uses language to orient or guide the students' conceptual activity in a desired direction to achieve the desired outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, the current social studies curriculum in Turkey was designed to adopt a research and inquiry-based learning strategy. With the implementation of this new curriculum, the teaching style required a reformulation by putting extra emphasis on classroom discourse where student contribution is of crucial importance because the in-class activities in this new system provide a chance for the students to meet and think about new/different perspectives [3]. In this new education system, an instructor's knowledge of the subject matter is critical, but not sufficient [4].…”
Section: Introductionmentioning
confidence: 99%